Dampak Pandemi COVID-19 terhadap Kegiatan Belajar Mengajar Daring - Dian Ramadan Lazuardi; Muhammad Kristiawan (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2022)
This study aims to describe the impact of the COVID-19 pandemic on implementing online teaching and learning activities. The type of research used is a qualitative exploratory case study based on five Biology Education Study Program students. Data collection techniques were interviews, video/audio recordings and literature studies which were analyzed through data reduction, data presentation and concluding. The results showed that during online learning activities, the applications used were zoom meeting, google meeting, google classroom and WhatsApp group. The obstacles that arise during the teaching and learning activities are students and lecturers who have not been able to adapt to technology, unstable telecommunication networks fully, students are less active in attending lectures, and anxiety arises in students with assignments given by lecturers. In conclusion, lecturers and students are not fully ready to carry out online learning, so the teaching and learning process is not optimal. Keywords: COVID-19, Biology Students, Online Learning